Implementasi Manajemen Diri Dalam Meningkatkan Keberhasilan Berwirausaha Pada UMKM Jamur ” Tiga Saudara” Desa Kalikesur - Pujiastuti, Ratna; Sumantri, Edi; Achadi, Ady; Uripi, Cahyaningtyas Ria; Koesoemasari, Dian Safitri P (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Self-management is the ability to control oneself, including physical, emotional, feelings, thoughts and behavior, to achieve good and directed goals. Self-management is an important skill that can help a person achieve success and personal satisfaction. Self-management skills are very necessary for entrepreneurs. The service in Kalikesur Village takes the theme Implementation of Self-Management in Increasing Entrepreneurial Success. Activities were carried out for two days in the form of assistance and provision of spinners and digital scales. The owner of Mushroom Three Brothers UMKM is enthusiastic and motivated to further develop the business, especially with capital assistance in the form of a spinner and digital scales